2010
DOI: 10.1159/000316314
|View full text |Cite
|
Sign up to set email alerts
|

A Documentation System to Save Time and Ensure Proper Application of the Fiberoptic Endoscopic Evaluation of Swallowing (FEES®)

Abstract: A properly performed fiberoptic endoscopic evaluation of swallowing (FEES®) is comprehensive and time-consuming. Editing times of FEES protocols and attempts for efficiency maximization are unknown. Here, the protocol editing times of completed FEES examinations were determined. The present study reports the time savings and quality gains of a newly developed documentation system tailored to the FEES standard of Langmore. Four independent examiners analyzed twelve videos of FEES procedures, six without and six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 38 publications
0
7
0
7
Order By: Relevance
“…The procedure has also been used to good effect in research to measure the degree of swallow dysfunction and to test the effect of therapies. While protocols have been published and disseminated [ 52 ] further efforts to achieve standardization for scoring and interpretation of the exam are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure has also been used to good effect in research to measure the degree of swallow dysfunction and to test the effect of therapies. While protocols have been published and disseminated [ 52 ] further efforts to achieve standardization for scoring and interpretation of the exam are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…These studies used tools developed for generic usability studies, and questionnaires played an important role (1, 6, 8-9, 18, 25, 28, 34-36, 38). Efficiency of performing a certain system function was measured in several studies, mostly as time spent filling in a single form or searching a data item (N = 9, 23%) (1,6,9,14,18,28,(33)(34)(35).…”
Section: Indicatorsmentioning
confidence: 99%
“…Slower data entry was explained, e.g., by learning effects and increase in the amount of data (28). However, there were also studies which found that structured data is faster to enter (14,18) and makes work processes easier (36). Two articles by the same author described the effect of data organization on the data retrieval time; relatively small changes in the data structure may have a significant impact on the retrieval time (33,34).…”
Section: Indicatorsmentioning
confidence: 99%
“…In clinical studies of swallowing dysfunction, the incidence of both penetration and aspiration are associated with increased risk of developing pneumonia, which can be life threatening (1). The 8-Point Penetration-Aspiration Scale (PAS) (2), used in clinical research studies, is an established and validated instrument for measuring the airway protection during swallowing (37). No such scale, however, currently exists for animal models of swallowing dysfunction.…”
Section: Introductionmentioning
confidence: 99%